2022
DOI: 10.3390/d14080651
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Diversity of Arbuscular Mycorrhizal Fungi Associated with Two Cultivation Practices of Theobroma cacao

Abstract: In recent years, new data on the diversity of genera and species in the phylum Glomeromycota continue to be added and rearranged. Arbuscular mycorrhizal fungi are key to plant nutrition and agriculture. Studies report different short- and long-term cultivation practices that influence the abundance and diversity of Glomeromycota. To the best of our knowledge, there are no known studies of the fungal communities in the fine aroma cocoa cultivars. In this context, our work aims to discover the diversity of arbus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Glomus accounted for more than 50% of the identified T‐RFs at a genus level, in the six sites, while Acaulospora ranged from 19.0% in QV to 40.4% in QM. Glomus has been reported as a common and dominant genus found in different land use systems and altitudes (Flores et al, 2022 ; Guzman et al, 2021 ; Zhang et al, 2021 ). Our results support the studies that observed the occurrence of Glomus in a wide range of environmental conditions and ecological niches, showing the adaptability of this genus (Fall et al, 2022 ; Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomus accounted for more than 50% of the identified T‐RFs at a genus level, in the six sites, while Acaulospora ranged from 19.0% in QV to 40.4% in QM. Glomus has been reported as a common and dominant genus found in different land use systems and altitudes (Flores et al, 2022 ; Guzman et al, 2021 ; Zhang et al, 2021 ). Our results support the studies that observed the occurrence of Glomus in a wide range of environmental conditions and ecological niches, showing the adaptability of this genus (Fall et al, 2022 ; Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the effect of management practices and soil texture on microbial communities (Hamarashid et al, 2010 ; Flores et al, 2022 ; Zhang et al, 2019 ). In this study, more than 50% of the total T‐RFs were shared among management practices and soil textures, highlighting that there was a core of T‐RFs that are stable under different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the mycorrhization frequencies of the roots vary from 10% to 66% and the mycorrhization intensities of the roots vary from 10% to 40.5% on a total of one hundred (100) root fragments observed (Table 3). Mycorrhization (frequency and intensity) varies according to environmental factors of the localities and as a function of time [21] and not necessarily of spore abundance in the soil [53].…”
Section: Discussionmentioning
confidence: 99%
“…Cacao forms an association with AMF communities [18] [19] and selected species of these AMF significantly improve the overall growth of cacao seedlings [20]. In Cameroon, few studies have been made on cacao endogenous AMF as well as factors that can predict their diversity and abundance according to soil properties and altitude.…”
Section: Introductionmentioning
confidence: 99%